Antipsychotic treatment is associated with risk of atrial fibrillation: A nationwide nested case-control study. (15th January 2017) - Chou, Ruey-Hsing; Lo, Li-Wei; Liou, Ying-Jay; Shu, Jiah-Hwang; Hsu, Hsiu-Chuan; Liang, Ying; Huang, Chin-Chou; Huang, Po-Hsun; Lin, Shing-Jong; Chen, Jaw-Wen; Chan, Wan-Leong; Leu, Hsin-Bang
Abstract: Background: Antipsychotic agents are well known for their arrhythmigenic effect on ventricular arrhythmia. Though a few case reports observed the occurrence of atrial fibrillation (AF) after antipsychotic exposure, information about their implication in AF is limited. Methods: Based on the National Health Insurance Database in Taiwan, we conducted a nested case-control study to investigate the relationship between antipsychotics and AF. From 2001 to 2010, a total of 34, 053 cases of AF and 34, 919 matched controls were enrolled. Antipsychotic exposure was measured and binding affinity to neurotransmitter receptors was calculated. Both medical and psychiatric comorbidities were identified and adjusted in multivariate logistic regression analysis. Results: Current antipsychotic use was associated with a 17% increased risk of AF relative to nonusers (adjusted OR: 1.17, 95% CI: 1.10–1.26). A dose-dependent relationship of antipsychotic exposure and AF risk was observed ( P for trend < 0.001). Antipsychotics with higher binding affinity to muscarinic M2 receptors were associated with a higher incidence of AF. In subgroup analysis, subjects with preexisting hypertension, diabetes, or coronary artery diseases were at greater risk of developing AF following antipsychotic exposure. Conclusion: Antipsychotic exposure was associated with increased risk of AF, especially for agents with higher cardiac muscarinic receptor binding affinity. Physicians should monitor the occurrence of new-onset AF, and strictly control underlying medical risk factors while prescribing antipsychotic agents to high-risk populations.